Monte Carlo simulations for angular and spatial distributions in therapeutic-energy proton beams. (November 2017) - Lin, Yi-Chun; Pan, C.Y.; Chiang, K.J.; Yuan, M.C.; Chu, C.H.; Tsai, Y.W.; Teng, P.K.; Lin, C.H.; Chao, T.C.; Lee, C.C.; Tung, C.J.; Chen, A.E.
Abstract: The purpose of this study is to compare the angular and spatial distributions of therapeutic-energy proton beams obtained from the FLUKA, GEANT4 and MCNP6 Monte Carlo codes. The Monte Carlo simulations of proton beams passing through two thin targets and a water phantom were investigated to compare the primary and secondary proton fluence distributions and dosimetric differences among these codes. The angular fluence distributions, central axis depth-dose profiles, and lateral distributions of the Bragg peak cross-field were calculated to compare the proton angular and spatial distributions and energy deposition. Benchmark verifications from three different Monte Carlo simulations could be used to evaluate the residual proton fluence for the mean range and to estimate the depth and lateral dose distributions and the characteristic depths and lengths along the central axis as the physical indices corresponding to the evaluation of treatment effectiveness. The results showed a general agreement among codes, except that some deviations were found in the penumbra region. These calculated results are also particularly helpful for understanding primary and secondary proton components for stray radiation calculation and reference proton standard determination, as well as for determining lateral dose distribution performance in proton small-field dosimetry. By demonstrating these calculations, this work could serve as a guide to the recent field of Monte Carlo methods for therapeutic-energy protons. Highlights: Monte Carlo simulation for angular & spatial distributions of therapeutic proton. Thin targets and water phantom cases investigated using FLUKA, GEANT4 and MCNP6. Comparing the primary and secondary proton fluences and dosimetric differences. Inter-code discrepancies were found in the penumbra region. Results of lateral dose distributions are useful in proton small-field dosimetry.